AN ALGORITHM FOR FORECASTING EARTHQUAKE GROUND MOTION - Gusev A.A.; Petukhin A.G. (My University, 1996)
A first version of an algorithm is described designed to estimate expected strong ground motion due to earthquakes for use in civil engineering seismology. The algorithm has the following features: 1) the properties of seismic events in a seismic source zone are specified in either of three ways; 2) spectral levels and other parameters at arbitrary distances and magnitudes are found by making use of appropriate scaling laws for earthquake source parameters and spectral levels, as well as of attenuation and scattering parameters; 3) site conditions are incorporated through a set of corrections to the Fourier spectrum for soils of categories 2 and 3 relative to category 1. The block diagram of the algorithm is presented and examples are given.